Cyclical Properties of Workers’ Remittances: Evidence from Bosnia and Herzegovina - IsakoviÄ‡, NedÅ¾ad; Ilgün, Erkan (International Journal of Economics and Financial Issues, 2014)
Workers’ remittances are proven to positively influence the receiving economies and to help the receivers of remittances to cope with currency constraints and unemployment in the receiving country. Remittances can also improve the capability of the receiving economies to mitigate the negative effects of economic downturns and crisis by having counter-cyclical relationship in accordance to the GDP of receiving countries. This is the general opinion, but the latest reports say that they could behave in pro-cyclical manner. In the light of these facts, this article investigates the nature of co-movement of cyclical components, thus investigating cyclicality, between remittance inflow and output or GDP of B&H. This article also investigates cyclical properties of Official Development Assistance and Foreign Direct Investment inflow between Bosnian output in order to determine whether one of other two external financial flows could be used as a mitigating tool of negative aspect of economic downturn in B&H. Keywords: Remittances and B&H; Cyclical properties of workers’ remittances JEL Classifications: E32; F24